2019
DOI: 10.1002/dc.24164
|View full text |Cite
|
Sign up to set email alerts
|

Cytological features of basal cell adenoma of salivary glands: Analysis of 19 cases emphasizing stromal spindle cells

Abstract: Background Basal cell adenoma (BCA) of the salivary gland is a relatively rare benign tumor. Although the presence of stromal spindle cells is a characteristic histopathological feature, this finding has not been the focus of much attention in the cytodiagnosis of BCA. Thus, we analyzed the cytological features of BCA, especially the presence of stromal spindle cells. Methods Patients who were histopathologically diagnosed with BCA and underwent preoperative fine‐needle aspiration cytological examination were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Hara et al reported that six of nine basal cell adenoma specimens had stromal spindle cells, but these cells were not observed in BAC (two cases), adenoid cystic carcinoma (10 cases), myoepithelioma (four cases), and pleomorphic adenoma (five cases) specimens . Our previous study demonstrated that stromal spindle cells were present in the cytological specimens of 85.7% of histology‐proven stromal spindle cells‐positive basal cell adenoma cases and 63.2% of all basal cell adenoma cases . Taken together, the data indicate that stromal spindle cells are frequently present in the cytological specimens of both basal cell adenoma and BAC cases.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Hara et al reported that six of nine basal cell adenoma specimens had stromal spindle cells, but these cells were not observed in BAC (two cases), adenoid cystic carcinoma (10 cases), myoepithelioma (four cases), and pleomorphic adenoma (five cases) specimens . Our previous study demonstrated that stromal spindle cells were present in the cytological specimens of 85.7% of histology‐proven stromal spindle cells‐positive basal cell adenoma cases and 63.2% of all basal cell adenoma cases . Taken together, the data indicate that stromal spindle cells are frequently present in the cytological specimens of both basal cell adenoma and BAC cases.…”
Section: Discussionmentioning
confidence: 47%
“…Stromal spindle cells are considered a characteristic feature of basal cell adenoma . Although these cells can also be present in BAC, the precise incidence of the presence of stromal spindle cells in BAC remains unclear .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations